Overexpression of the crp gene promotes biofilm formation and increases antibiotic resistance in bovine-derived Klebsiella pneumoniae - Zhang, Ying; Qi, Jiancheng; Gu, Li; Yi, Sirun; Liu, Yani; Zhang, Keyue; Guo, Linqi; Zuo, Zhicai (Frontiers in Microbiology, 2026)
BackgroundThe multidrug resistance of bovine-derived Klebsiella pneumoniae is a significant concern, with biofilm formation serving as a major factor in the escalation of antibiotic resistance. The function of cAMP receptor protein (CRP), which is encoded by the crp gene and acts as a central regulator of environmental sensing and virulence, remains unclear in pathogenic strains derived from livestock.PurposeThis study aims to investigate the influence of CRP overexpression on biofilm formation and antibiotic resistancein bovine-derived Klebsiella pneumoniae, with a particular focus on its effect against cotrimoxazole.MethodsRecombinant strains with constitutive (Pkan) and inducible (Ptac) promoter-driven CRP overexpression were constructed using molecular cloning. Gene and protein expression were validated using RT-qPCR and immunoblotting analyses. Biofilm formation was quantified by crystal violet staining, antibiotic susceptibility to 23 agents was assessed using the Kirby-Bauer disk diffusion method, and metabolic burden was evaluated through growth curve analysis.ResultThe CRP-overexpressing strain (KAN group) showed a 2.9-fold increase in CRP protein expression (p < 0.01) and a significant enhancement in biofilm formation (p < 0.0001), without significant impact on bacterial growth. Notably, a reversal in antibiotic susceptibility was observed: while the wild-type strain was sensitive to cotrimoxazole (inhibition zone: 22 mm), the CRP-overexpressing strain displayed complete resistance (inhibition zone: 7 mm).ConclusionOverexpression of CRP protein promotes biofilm formation and confers resistance to cotrimoxazole in bovine-derived Klebsiella pneumonia, indicating that CRP-mediated biofilm formation might be a key mechanism driving the observed cotrimoxazole resistance in this strain.